Evaluation of Pseudomonas aeruginosa exotoxin A and elastase as virulence factors in acute lung infection. - Blackwood, L L (1983)
Acute Pseudomonas aeruginosa pneumonia was established in guinea pigs by intratracheal instillation of bacteria. Challenge strains included PAO-1, a strain known to produce exotoxin A, alkaline protease, and elastase, and several PAO-1 mutants deficient in either biologically active exotoxin A or elastase production. Survival, intrapulmonary killing of bacteria, and blood cultures were compared among the groups. Strains of P. aeruginosa deficient in active elastase production appeared to be less virulent than the parent strain and were more easily cleared from the lung. Opposite results were obtained for the exotoxin A-deficient mutants. These data suggest that elastase, but not exotoxin A, was an important virulence factor during acute pneumonia due to P. aeruginosa.